Polymorphisms of the serotonin receptors genes in patients with bruxism: a systematic review - Campello, Camilla Porto; Moraes, Sandra Lúcia Dantas; Vasconcelos, Belmiro Cavalcanti do Egito; Lima, Elker Lene Santos de; Pellizzer, Eduardo Piza [UNESP]; Lemos, Cleidiel Aparecido Araújo; Muniz, Maria Tereza Cartaxo (FapUNIFESP (SciELO), 2022)
This study aimed to investigate if SNP rs6313, SNP rs2770304, SNP rs4941573, and SNP rs1923884 of the 5-HT2A receptor gene and SNP rs6295 of the 5-HT1A receptor gene are associated with bruxism etiology. METHODOLOGY: This systematic review was registered in PROSPERO (CRD42018094561). A search was conducted for articles published in or before May 2021. To qualify for eligibility in this review, the studies had to be case-controls, cohort or cross-sectional. The inclusion criteria were the articles with a group of patients with bruxism and a control group in which the presence of these SNPs was evaluated. The exclusion criteria were the investigations of other polymorphisms, the studies that did not consider a control group for comparison, case reports, and reviews. The NOS and JBI were used to evaluate the methodological quality of studies. RESULTS: We conducted this study with databases, such as Web of Science, Scopus, Embase, PubMed/MEDLINE, and ProQuest. We considered four studies eligible. A total of 672 participants were included,187 with sleep bruxism, 105 with awake bruxism, 89 with sleep and awake bruxism, and 291 controls. One study found a strong association between the SNPs rs6313, rs2770304 and rs4941573 of the 5-HT2A receptor gene and sleep bruxism. In one study, we considered the C allele of the SNP rs2770304 a risk factor for sleep bruxism. We found no significant results of other SNPs in sleep bruxers compared to controls. We found no positive association concerning the SNPs and groups of awake bruxism and sleep and awake bruxism. CONCLUSION: The different results regarding the SNPs in sleep bruxers could be explained by the genetic distinction between Chilean, Mexican, Japanese, and Polish population. More clinical trials and prospective studies must be conducted with larger sample size and in different ethnicities to confirm the results of this review.